2012
DOI: 10.1002/ldr.2142
|View full text |Cite
|
Sign up to set email alerts
|

Historical landscape photographs for calibration of Landsat land use/cover in the northern Ethiopian highlands

Abstract: The combined effects of erosive rains, steep slopes and human land use have caused severe land degradation in the Ethiopian highlands for several thousand years, but since the 1970s however, land rehabilitation programs have been established to reverse deterioration. In order to characterize and quantify the transformations in the north Ethiopian highlands, a study was carried out over 8884 km² of the Tigray highlands of northern Ethiopia. Using Landsat Multi Spectral Scanner and later Thematic Mapper imagery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 53 publications
(78 reference statements)
1
65
1
Order By: Relevance
“…In order to secure food production, farmers were forced to cultivate steeper land and overgrazing removed most of vegetation from the hillslopes. Analyses of region-wide land use and cover on the basis of Landsat imagery by de Mûelenaere et al (2013) in the 1970s and 1980s confirmed that in 1984/1986, the area covered by bare soil was extensive and that the area covered by cropland peaked. From the analysis of land use and land cover on old terrestrial photographs, Meire et al (2013) also indicated a minimum in vegetation cover in the period 1940s-1990s.…”
Section: Hydrogeomorphic Phases and The Role Of Land Use And Precipitsupporting
confidence: 51%
See 1 more Smart Citation
“…In order to secure food production, farmers were forced to cultivate steeper land and overgrazing removed most of vegetation from the hillslopes. Analyses of region-wide land use and cover on the basis of Landsat imagery by de Mûelenaere et al (2013) in the 1970s and 1980s confirmed that in 1984/1986, the area covered by bare soil was extensive and that the area covered by cropland peaked. From the analysis of land use and land cover on old terrestrial photographs, Meire et al (2013) also indicated a minimum in vegetation cover in the period 1940s-1990s.…”
Section: Hydrogeomorphic Phases and The Role Of Land Use And Precipitsupporting
confidence: 51%
“…Several studies indeed indicate that vegetation cover and land management strongly improved in recent decades (e.g. Gebremedhin et al 2004;Munro et al 2008;Alemayehu et al 2009;Mekuria et al 2009;Nyssen et al 2009;de Mûelenaere et al 2013;Meire et al 2013). As a reaction to severe land degradation that stroke northern Ethiopia in the 1970s and 1980s, environmental rehabilitation programs were launched with the aim of increasing land resilience to the effects of droughts.…”
Section: Hydrogeomorphic Phases and The Role Of Land Use And Precipitmentioning
confidence: 97%
“…Next, there have been widespread reforestation programs undertaken in recent years by the Ethiopian government and so forests and reforestation as a mechanism for decreasing soil erosion is a dominant theme in agricultural programs, especially in the highlands. This is echoed by Mûelenaere et al, (2012) who used historical photos and Landsat satellite imagery to detect land use and land cover changes in the Ethiopian Highlands. They found that over thirty years, bare soil areas had been reduced to a quarter of their original area and that while natural forest decreased slightly, overall vegetation cover had increased with Eucalyptus spp.…”
Section: Resultsmentioning
confidence: 97%
“…Land use is closely related to land cover, in which the former occurs on the surface of the Earth and the latter is the product of various surface processes including land use (Verburg et al, 2014). Land use and land cover have particular time and space attributes, and their form and feature change in a variety of space and time scales, which generates a series of ecological environmental effects (de Mûelenaere et al, 2014). For instance, El-Kawy et al (2011) analyzed the categories of land use and cover using satellite images, which provided a theoretical basis for a land management scheme proposal.…”
Section: Introductionmentioning
confidence: 99%